Bridging genomics research between developed and developing countries: the Genomic Medicine Alliance. (September 2014) - Cooper, David N; Brand, Angela; Dolzan, Vita; Fortina, Paolo; Innocenti, Federico; Michael Lee, Ming Ta; Macek, Milan; Al-Mulla, Fahd; Prainsack, Barbara; Squassina, Alessio; Vayena, Effy; Vozikis, Athanassios; et al.
The Genomic Medicine Alliance is a global academic research network that aims to establish and strengthen collaborative ties between the various genomic medicine stakeholders. Its focus lies on the translation of scientific research findings into clinical practice. It brings together experts from disciplines including genome informatics, pharmacogenomics, public health genomics, ethics in genomics and health economics, and it is supervised by a 14-member International Scientific Advisory Committee comprising internationally renowned scientists. The Alliance's official journal, Public Health Genomics, offers members a highly respected publication forum for their original research findings. In the short-to-medium term, the Genomic Medicine Alliance hopes to harmonize research activities between developed and developing countries and to organize educational activities in the field of genomic medicine.